Expanding the sum of all human knowledge: Wikipedia, translation and linguistic justice. (3rd April 2017) - McDonough Dolmaya, Julie
ABSTRACT: The Wikimedia Foundation is arguably the quintessential example of a socially responsible organisation: not-for-profit, dedicated to the growth, development and distribution of free, multilingual content, the Foundation operates openly editable projects like Wikipedia, which now has anywhere from one to several million articles available in more than 280 languages. Wikimedia – the organisation that hosts and operates Wikipedia – does not appear to have an explicit translation policy. This paper therefore begins by assessing the organisation's Language Proposal Policy and Wikipedia's translation guidelines. Then, drawing on statistics from the Content Translation tool recently developed by Wikipedia to encourage translation within the various language versions, this paper applies the concept of linguistic justice to help determine how any future translation policies might achieve a better balance between fairness and efficiency, arguing that a translation policy can be both fair and efficient, while still conforming to the 'official multilingualism' model that seems to be endorsed by the Wikimedia Foundation.